The Effectiveness of the Practicum Video Guide on Distance Learning in Improving Biology Learning Outcomes in Enzyme Content - Hofifah, Siti Nur; Sumiati, S. (Indonesian Journal of Teaching in Science, 2023)
This study aims to analyze the effectiveness of video practicum guides on distance learning in improving biology learning outcomes on enzymes. This research was conducted with the stages of problem identification, planning, action (cycles I-III), observation, and reflection. All stages of learning were carried out in distance learning (online). The research was conducted on 35 students at a high school in Bandung. The assessment instrument in this study consisted of observation sheets and students' cognitive tests at the end of the cycle. The results of observations and cognitive tests of students showed that the average score for the biological value of the enzyme material had increased. There was a significant increase in each cycle, showing the success of the learning strategy by listening to video practicum. Student learning outcomes were also influenced by the teacher management in carrying out the online learning process. This research was expected to provide new information regarding the use of video media in distance learning.